2019
DOI: 10.4209/aaqr.2019.04.0184
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Low-temperature NH3-SCR Activity over Ce-Ti Oxide Catalysts by Hydrochloric Acid Treatment

Abstract: The effect of hydrochloric acid treatment on Ce-Ti oxides was investigated for selective catalytic reduction of NO with NH 3. The results showed that hydrochloric acid treatment had a positive effect on the low-temperature activity of Ce-Ti oxides. The improved activity of Ce-Ti oxides could be attributed to the increase in the concentration of Ce as well as the amount of Ce 3+ and chemisorbed oxygen on the catalyst surface. In addition, the enhanced Lewis acidity could improve NH 3 absorption, and was also a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For this purpose, many catalysts containing metal oxides have been found to possess high catalytic activity for SCR reaction including Fe, Ce, Mn, and Cu based catalysts. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on our previous study, we found the Fe-Ce/Ti catalysts could exhibit high catalytic activity for the NH 3 -SCR reaction. However, there are several components in the real ue gases including K, Ca, CO 2, and SO 2 , which will lead to the physical or chemical deactivation of catalysts and thus restrict the industrial application of catalysts.…”
Section: Introductionmentioning
confidence: 89%
“…For this purpose, many catalysts containing metal oxides have been found to possess high catalytic activity for SCR reaction including Fe, Ce, Mn, and Cu based catalysts. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on our previous study, we found the Fe-Ce/Ti catalysts could exhibit high catalytic activity for the NH 3 -SCR reaction. However, there are several components in the real ue gases including K, Ca, CO 2, and SO 2 , which will lead to the physical or chemical deactivation of catalysts and thus restrict the industrial application of catalysts.…”
Section: Introductionmentioning
confidence: 89%
“…Carbon materials, including activated carbon, graphene, carbon nanotubes etc., have found wide application for use in low temperature SCR, because of their high specific surface areas and chemical stability (Marban et al, 2004;Lu et al, 2010;Zhu et al, 2011;Jiao et al, 2015;Yu et al, 2015). In particular, the manganese oxide catalysts have attracted great attention, because they contain various types of labile oxygen and oxidation states of Mn (Jiang et al, 2019b;Zhang et al, 2019;Tong et al, 2020;Wang et al, 2020). This improves the feasibility of the use of these catalysts to complete the catalytic cycle in low temperature NH3-SCR.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Jiang et al. found that similar enhancement can be obtained by treating Ce−Ti sample with desired aqueous hydrochloric acid solution [97] . Since CeO 2 −TiO 2 sample is also a good photocatalyst, thus we have adopted a photo‐treatment to enhance its NH 3 −SCR activity [21b,98] .…”
Section: Methods In Improving the Catalytic Activity Of Ceo2−tio2 Catmentioning
confidence: 73%
“…A study conducted by Jiang et al found that similar enhancement can be obtained by treating CeÀ Ti sample with desired aqueous hydrochloric acid solution. [97] Since CeO 2 À TiO 2 sample is also a good photocatalyst, thus we have adopted a photo-treatment to enhance its NH 3 À SCR activity. [21b,98] For CeO 2 /TiO 2 catalyst, photo-treatment can induce a stronger interaction between CeO 2 and TiO 2 and the formation of new oxygen vacancies and Ce 3 + ions.…”
Section: Pretreatmentmentioning
confidence: 99%